THE HABITAT MAPPING IN SLOV ENIA - CONNECTION TO THE VEGETATION - SELISKAR, A. (Annali di Botanica, 2011)
A short history of vegetation researches in Slovenia is given in connection with the habitat mapping. Syntaxonomical units are compared to the units of Palearctic habitat classification (former Corine) and Natura 2000. The need of harmonisation has been found in some cases for all for the syntaxonomical units with southeastern distribution, i.e. alliances and suballiances Aremonio-Fagion (Ht. 1938) Török, Podani et Borh. 1989, Epimedio-Fagenion Marincek et al. 1993, Lamio orvalae- Fagenion Borh. ex Marincek et al. 1993, Saxifrago rotundifoliae-Fagenion Marincek et al. 1992 or Fraxino orni-Ostryion carpinifoliae Tomazic 1940, Orno-Ericion Ht. 1958, Orno-Ericenion Ht. (1957) 1958 and other. The missing units have been described. Proposed is the use of more exact names for habitat units.